2018
DOI: 10.3389/fnagi.2018.00267
|View full text |Cite
|
Sign up to set email alerts
|

p58IPK Is an Endogenous Neuroprotectant for Retinal Ganglion Cells

Abstract: p58IPK is an endoplasmic reticulum (ER)-resident chaperone playing a critical role in facilitating protein folding and protein homeostasis. Previously, we have demonstrated that p58IPK is expressed broadly in retinal neurons including retinal ganglion cells (RGCs) and loss of p58IPK results in age-related RGC degeneration. In the present study, we investigate the role of p58IPK in neuroprotection by in vitro and in vivo studies using primary RGC culture and two well-established disease-relevant RGC injury mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
(33 reference statements)
3
12
0
Order By: Relevance
“…Non-adherent cells were incubated with mouse Thy-1.2 antibody (BD Biosciences) to isolate ganglion cells (McLaughlin, Dhimal, Li, Wang, & Zhang, 2018). The primary murine RGCs were seeded at a density of 3 × 10 5 cells per well.…”
Section: Primary Culture Of Mouse Rgcsmentioning
confidence: 99%
“…Non-adherent cells were incubated with mouse Thy-1.2 antibody (BD Biosciences) to isolate ganglion cells (McLaughlin, Dhimal, Li, Wang, & Zhang, 2018). The primary murine RGCs were seeded at a density of 3 × 10 5 cells per well.…”
Section: Primary Culture Of Mouse Rgcsmentioning
confidence: 99%
“…Therapeutic effects of MANF are mainly mentioned in Parkinson's disease, neurodegenerative diseases and cerebral stroke 12,14‐19 . Recently, more and more studies show that MANF not only affects neuron cells but also affects immune function, 20 hepatocellular carcinoma (HCC), 21 retinal development, 22 food intake and nephrotic syndrome 23 . Our previous study showed that MANF was extensively expressed in liver, and it was up‐regulated in para‐cancer tissue and down‐regulated in cancer tissues in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…They showed increased P58 IPK expression during stress in WT mice, whereas stress enhanced apoptosis in retinal ganglion cells in the KO mice, suggesting a protective role of P58 IPK on retinal neurons during ER stress 29. McLaughlin et al recently showed that loss of p58 IPK led to reduced mRNA expression, but not the protein level, of mesencephalic astrocyte-derived neurotrophic factor (MANF), a neurotrophic factor that resides in the ER 30. Extensive investigation of nervous system in the animal model of DNAJC3 (P58 IPK ) KO is lacking.…”
mentioning
confidence: 99%